Multiplex detection of urinary miRNA biomarkers by transmission surface plasmon resonance. Issue 19 (6th September 2018) - Yeung, Wing Kiu; Chen, Huai-Yi; Sun, Juan-Jie; Hsieh, Tung-Han; Mousavi, Mansoureh Z.; Chen, Hsi-Hsien; Lee, Kuang-Li; Lin, Heng; Wei, Pei-Kuen; Cheng, Ji-Yen
Abstract : The clinical assessment of short-stranded nucleic acid biomarkers such as miRNAs could potentially provide useful information for monitoring disease progression, prompting definitive treatment decisions. Abstract : The clinical assessment of short-stranded nucleic acid biomarkers such as miRNAs could potentially provide useful information for monitoring disease progression, prompting definitive treatment decisions. In the past decade, advancements in biosensing technology have led to a shift towards rapid, real-time and label-free detection systems; as such, surface plasmon resonance (SPR) biosensor-based technology has become of high interest. Here, we developed an automated multiplex transmissive surface plasmon resonance (t-SPR) platform with the use of a capped gold nanoslit integrated microfluidic surface plasmon resonance (SPR) biosensor. The automated platform was custom designed to allow the analysis of spectral measurements using wavelength shift (d λ ), intensity (d I ) and novel area change (d A ) for surface binding reactions. A simple and compact nanostructure based biosensor was fabricated with multiplex real-time detection capabilities. The sensitivity and specificity of the microfluidic device was demonstrated through the use of functionalised AuNPs for target molecule isolation and signal enhancement in combination with probes on the CG nanoslit surface. Our work allows for the multiplex detection of miRNA at femtomolar concentrations in complex media such as urine.